2014
DOI: 10.1371/journal.pone.0106440
|View full text |Cite
|
Sign up to set email alerts
|

Local and Systemic RAGE Axis Changes in Pulmonary Hypertension: CTEPH and iPAH

Abstract: ObjectiveThe molecular determinants of chronic thromboembolic pulmonary hypertension (CTEPH) and idiopathic pulmonary arterial hypertension (iPAH) remain poorly understood. The receptor for advanced glycation endproducts (RAGE) and its ligands: HMGB1 and S100A9 are involved in inflammatory disorders. We sought to investigate the role of the RAGE axis in patients with CTEPH undergoing pulmonary endarterectomy (PEA), iPAH undergoing lung transplantation (LuTX). The high pulmonary vascular resistance in CTEPH/iPA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 67 publications
1
24
0
1
Order By: Relevance
“…25) From their report and our results, the essential role of HMGB1 and soluble RAGE might be different between idiopathic PAH and CTEPH patients. Few reports have demonstrated an association between RAGE, HMGB1 and CTEPH, therefore, the role of HMGB 1 and soluble RAGE in CTEPH patients might be an important research target in the future.…”
Section: Discussionmentioning
confidence: 53%
“…25) From their report and our results, the essential role of HMGB1 and soluble RAGE might be different between idiopathic PAH and CTEPH patients. Few reports have demonstrated an association between RAGE, HMGB1 and CTEPH, therefore, the role of HMGB 1 and soluble RAGE in CTEPH patients might be an important research target in the future.…”
Section: Discussionmentioning
confidence: 53%
“…15 Endarterectomized tissues from patients with CTEPH show vessel-like structures in material obtained from distal areas, whereas proximal material is characterized by lower cell density and sometimes the accumulation of fresh thrombotic material. 16 In this study, we aimed to establish whether NET formation is a feature of vascular pathology in CTEPH and PAH, study the effects of NETs on pulmonary endothelial and smooth muscle responses in vitro, and investigate the signaling mechanisms involved. We are the first to document NET formation in CTEPH and PAH and show that NETs trigger inflammatory activation of pulmonary endothelial cells and promote endothelial angiogenesis in vitro and in vivo via myeloperoxidase/ H 2 O 2 /nuclear factor κB (NFκB)/TLR4-dependent signaling.…”
mentioning
confidence: 99%
“…Moser, et al actually demonstrated that there were no significant differences in sRAGE levels before and after pulmonary endarterectomy. 8) They reported similar findings in patients with IPAH who underwent lung transplantation. This discrepancy may be partly attributed to the properties of RAGE that have multiple ligands.…”
Section: Article P234mentioning
confidence: 65%
“…7) Moser, et al also reported that sRAGE levels were significantly higher in patients with idiopathic PAH (IPAH) and CTEPH than in controls. 8) On the other hand, they elucidated that significant elevation of HMGB1 was observed in patients with CTEPH but was not observed in patients with IPAH. Suzuki, et al also demonstrated that sRAGE levels had significant correlation with tricuspid valvular regurgitation pressure gradient (TRPG) while HMGB1 levels did not have significant correlation with TRPG.…”
Section: Article P234mentioning
confidence: 99%